On the interactions between tropical convection and gravity waves: comparisons between simple models and numerical simulations - Tulich, Stefan, author; Randall, David, advisor; Schubert, Wayne, committee member; Montgomery, Mike, committee member; Tavener, Simon J., committee member (Colorado State University. Libraries, 2003)
The interactions between tropical convection and atmospheric waves are investigated in an idealized, i.e., two-dimensional (2D) and non-rotating, framework. A primary goal is to determine whether and, if so, how tropical convection can "spontaneously" become organized through gravity wave dynamics. This will provide important groundwork for future studies aimed at improving the representation of tropical convective variability in numerical weather and climate prediction models. The dissertation is made up of three parts. The first investigates the linear response of an initially motionless tropical atmosphere to a spatially and temporally localized deep convective heat source. Consistent with output from high-resolution numerical simulations, results show that the heat source tends to strongly excite gravity wave packets with phase speeds in the range 35-45 m s-1 and 16-20 m s-1, and that the passage of the faster-(slower-) moving packets should tend to inhibit (favor) the development of additional deep convection. Part II discusses a linear tropical wave model in which vertical structure is truncated to include just two vertical normal modes: a fast-moving (first internal) mode and a slow-moving (second internal) mode. Based on the notion that deep convective development is strongly inhibited by the effects of dry air entrainment, anomalies in deep convective heating are assumed to be directly proportional to anomalies in column-integrated moisture. The model predicts that convectively coupled gravity waves, with realistic phase speeds and vertical temperature structures, should spontaneously develop from random initial conditions, even in the absence of a mean flow. Owing to an assumed temporal lag of stratiform precipitation processes with respective to deep convection, the largest growth rates of the unstable waves are found to occur at a wavelength of about 2000 km. In Part III, a vertical normal mode transform algorithm is used to analyze the structure and energetics of large-scale [O(1000 km)] convectively coupled gravity waves that spontaneously develop in a 2D cloud resolving model simulation of radiative convective equilibrium. Results show that the simulated waves primarily owe their existence to an unstable interaction between convection and modes with phase speeds in the range 16-18 m s-1 (i.e., third internal modes). Stratiform heating processes are found to play an important role in maintaining the energy of these modes, in agreement with the stratiform instability theory. In contrast to this theory, however, deep convective heating processes also play an important role.
Keywords: atmosphere; geophysics